Education Policies and Dalit Inclusion in Nepal: Uncovering Inequality, Exclusion and Structural Barriers - Chalaune, Bhawan Singh (KMC Journal, 2025)
The Dalits have historically been considered untouchable in the traditional caste system of Nepal, excluding them from mainstream education. In this context, this study critically analyses Nepal’s education policies and approaches to the Dalits’ inclusion and access to education. Drawing information from the recorded documents as policy document analysis, this qualitative study discusses the provisions regarding exclusive and inclusive educational policies and practices in Nepal’s education system. After the establishment of democracy in Nepal in 1951, schools were opened to the general public, including the Dalits. Since the 1980s, there have been efforts to bring the Dalits into the mainstream education system. However, reproduction of caste-based discrimination in policymaking has challenged the complete inclusion of the Dalits in education. Although the policies encouraging the oppressed people in the field of education have helped them in schooling, they are still inadequate. The education policy of Nepal has evolved in rhetoric but continues to fall short in practice. The persistence of caste-based discrimination and neglecting cultural capital in schooling indicates that without principled, structural changes, Dalit exclusion in education will persist. Bridging this gap requires critical engagement with both policy and practice through inclusive, justice-oriented frameworks informed by structural and cultural theories. Both policies and practices are necessary to reduce caste-based discrimination and poverty, change social and school practices, modify curricula and work collaboratively. Developing effective policy and practice for inclusion is a valuable commitment. Therefore, this suggests restructuring the education system changing the mindset of the policy makers, planners and teachers.